2001
DOI: 10.1016/s0370-2693(01)01190-x
|View full text |Cite
|
Sign up to set email alerts
|

Partonic scattering cross sections in the QCD medium

Abstract: A medium modified gluon propagator is used to evaluate the scattering cross section for the process gg → gg in the QCD medium by performing an explicit sum over the polarizations of the gluons. We incorporate a magnetic sreening mass from a non -perturbative study. It is shown that the medium modified cross section is finite, divergence free, and is independent of any ad-hoc momentum transfer cut-off parameters. The medium modified finite cross sections are necessary for a realistic investigation of the produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…However, in the medium, the medium modified resumed gluon propagator removes this infrared divergence and the typical finite differential cross section becomes [19] dσ dt = 9πα 2…”
Section: Ratio Of Characteristic Relaxation Time Of the Non-equilibrimentioning
confidence: 99%
“…However, in the medium, the medium modified resumed gluon propagator removes this infrared divergence and the typical finite differential cross section becomes [19] dσ dt = 9πα 2…”
Section: Ratio Of Characteristic Relaxation Time Of the Non-equilibrimentioning
confidence: 99%
“…Here φ ab and θ ab depend on k as well as on the tensors κ, ψ, t and u. The form (43) implies that [A µ , A ν ] and [A µ , F στ ] in equations (18), (19) are quadratic in the external field and have to be dropped out thus simplifying the currents S ν and R ν to…”
Section: In-medium Yang-mills Equationsmentioning
confidence: 99%
“…From the analysis of the phenomenon of color superconductivity of hadron matter at high density [16,17], it has been found that the medium surrounding the liberated quarks exhibits a polarization behavior characterized by an effective color dielectric constant ǫ ≫ 1, the magnetic permeability remaining close to one. The estimate ǫ ≫ 1 has also been obtained in [18] evaluating the photon self-energy for a color superconductor. The case of two-flavor color superconductor with prescribed dielectric susceptibility and magnetic permeability of the medium was considered by D. Litim and C. Manuel [19] applying the methods of transport theory and extending the results of Rischke, Son and Stephanov to finite temperature.…”
Section: Introductionmentioning
confidence: 97%
“…This divergence is inevitable as long as we use the free propagator in vaccuum to evaulate the Feynman diagrams. However, this infrared divergence can be removed when one uses medium modified propagators instead of the vacuum propagator to evaluate the collision term in medium [18][19][20]8,21]. The medium modified propagtaors have been obtained in the thermal field theory for the case of an equilibrium plasma.…”
Section: Introductionmentioning
confidence: 99%